ENHANCHING DISASTER PREPAREDNESS THROUGH GAMIFICATION: THE MISSION: RESILIENCE PROGRAM IN KENDARI CITY HIGH-RISK SCHOOLS - Saptaputra, Syawal Kamiluddin; Salsabila, Syefira; Akifah, Akifah; Mustaqim, Mustaqim; Ramadhan, Muh. Rahmat; Sagala, La Ode Hasnuddin S. (LPPM Univ. Ibn Khaldun Bogor, 2024)
This study aims to enhance disaster preparedness knowledge and skills among high school teachers and students in Kendari, Southeast Sulawesi, through a gamified educational approach called